Analisis Pengaruh Flexible Hrm Terhadap Firm Innovativeness Yang Dimediasi Innovative Work Behavior (Studi Kasus Pada Pt Xyz) - Kevin Matthew Aditya (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Innovation is one of the strategic prerequisites for companies if they want to have an advantage in competition. But to realize this is not easy, because it must also be supported by the flexibility of human resource management and employee behavior that must also be innovative. Based on this background, the purpose of this study was to analyze the direct influence of Flexible HRM, and Innovative Work Behavior on Firm Innovativeness; and the indirect effect of Flexible HRM on Firm Innovativeness through Innovative Work Behavior. This research approach is quantitative, with a type of causal research. The population is all PT XYZ permanent employees in Jakarta, totaling more than 700 employees, and a sample of 100 employees. The sampling technique is incidental sampling. Techniques for collecting data through face-to-face surveys, using questionnaires on a 1-5 Likert scale. Data analysis methods are descriptive analysis, multiple linear regression, and path analysis. The results showed that Flexible HRM and Innovative Work Behavior had a positive and significant effect on Firm Innovativeness. In addition, Innovative Work Behavior proved to play a role in mediating the influence of Flexible HRM on Firm Innovativeness.